PENGARUH LATIHAN FARTLEK DAN INTERVAL TERHADAP PENINGKATAN VO2MAX PEMAIN FUTSAL BERKAH UNITED MERANGIN - Deka Ismi Mori Saputra; Khairul Saleh; Yozi Andra (LP3M Universitas Muhammadiyah Muara Bungo, 2022)
This research is motivated by the low physical ability of the Berkah United Merangin Futsal players, this study aims to determine whether or not there is an effect of Fartlek training to increase VO2Max, There is or not the effect of Interval training increase VO2Max, and see whether there is a difference between Fartlek and Interval training on increasing VO2Max in Futsal Players in Merangin District. This research was conducted using an experimental method with a two-group pretest-posttest design. The population in this study was 12 Futsal Players at Berkah United Merangin The sampling technique was total sampling. The sample in this study was 12 Berkah United Merangin Futsal Players with 16 treatments. The research instrument uses a multi-stage fitness test. The data analysis technique used in this study was the t-test to determine the comparison between Fartlek and Interval exercises in increasing VO2Max. Based on the results of the study that there is an effect of Fartlek training to increase VO2Max in Berkah United Merangin Futsal Players, as evidenced by the value of count (5.291) > table (2.705). There is an effect of increasing VO2Max on Berkah United Merangin Futsal Players with Interval training, as evidenced by the value of count (9.231) > table (2.705). There is no significant difference between Fartlek Training and Interval Training to increase VO2Max on Berkah United Merangin Futsal Players because there is no significant difference in results, as evidenced by the value of count (0.622) < table (2.228).